Limiting The Age if Marriage in Indonesia: Harmonization Between Living Law and Positive Law - Khafid Abadi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2022)
The pattern of harmonization of the age limit for marriage in Indonesia between living law and positive law is described in this study. The purpose of this descriptive-analytic study is to provide a comprehensive explanation of the age limit for marriage from a variety of perspectives. The method of seeking to harmonize Islamic and positive law was then used to analyze and interpret the obtained data. Harmonization in limiting the age of marriage can be seen in three ways, according to the findings of this study: First, the philosophical differences between the two regarding how to interpret marriage's purpose. According to both positive and Islamic law, marriage is intended to benefit both parties. Second, Epistemological Considerations Islamic law provides an epistemological foundation for the government's age limit for marriage, siyasah syar'iyyah. Third, the legal aspect: despite the fact that positive law stipulates that a person must be 19 years old to get married, the state provides a marriage dispensation mechanism as an emergency exit for marriages performed before that age